WITH LOVE, YOURS TRULY: THE LANGUAGE OF SEDUCTION IN HENRY VIII’S LETTERS TO ANNE BOLEYN IN THE TUDORS SERIES - Arofa, Atika Rike; Setiyowidi, Angela Azzahra; Pangestu, Alfa Cahyo (Universitas Putera Batam, 2025)
This study examines the rhetorical strategies embedded in Henry VIII’s letters to Anne Boleyn as portrayed in the television series The Tudors. Drawing on Ballif’s seduction theory, which posits that persuasion intertwines rationality and emotional manipulation, the analysis identifies three key linguistic elements: affective, pompous, and ridiculous language. Using qualitative textual analysis paired with Spradley’s ethnographic coding techniques, the study investigates how Henry’s discourse oscillates between expressions of romantic devotion, performative grandiosity, and strategic dominance. The findings reveal that Henry’s letters employ emotional appeals, hyperbolic flattery, and rhetorical flourishes to simultaneously assert authority and court Anne’s favor. In contrast, Anne’s responses reflect caution and tactical modesty, underscoring her navigation of gendered power dynamics. The results demonstrate that seductive language in these exchanges blurs the boundaries between sincerity and manipulation, aligning with Ballif’s argument that rhetoric operates beyond binary distinctions of truth or falsehood. This study highlights the dual function of seduction as both an intimate gesture and a political instrument, offering fresh insights into the interplay of love, power, and persuasion in historical dramatizations.